Determination of infiltrative ductal breast carcinoma differentiation grade in biopsy imprints - Vukašinović-Bokun Zorana; Bokun Radojka; Tatomirović Željka (Vojnosanitetski Pregled)
Background/Aim. In patients with breast carcinoma there are many risk factors for assessment of breast carcinoma maturity and prognosis. Besides histological type of differentiation, cytologic criteria for the evaluation grade of the differentiation of infiltrative ductal breast carcinomas are very important for prognosis. The aim of this study was to define cytologic criteria for grading of infiltrative ductal carcinomas of the breast. Methods. The imprints of intraoperative biopsies from 124 patients were studied. They were air-dried and stained by May-Grünwald Giemsa method. The features assessed were: the degree and type of cell clustering, nuclear diameter and pleomorphism, chromatin structure, number and features of nucleoli, the aspect of cytoplasm, noncellular background and the variability of cells and nuclei. According to these morphologic features the infiltrative ductal carcinomas of the breast could be classified into three grades of differentiation. Results. Cytologic and histologic differentation grade revealed disagreement among 34.6% of the imprints. In 9 of total 23 histologicaly well differentiated carcinomas, cytological differentation grade was moderately differentiated. In 63 carcinomas with histologic differentiation grade II, cytologic differentiation grade was good in 12 and poor in 16 carcinomas. Conclusion. Cytologic and histologic grading were not identical in 34.6% of the imprints what points out the need to further definition of diagnostic criteria, especially for grade II of differentiation.